The New Keynesian Phillips Curve for a Small Open Economy - Pål Boug; Ådne Cappelen; Anders Rygh Swensen (Statistics Norway, Research Department, 2006)
The New Keynesian Phillips Curve (NKPC) has become the benchmark model for understanding inflation in modern monetary economics. One reason for the popularity is the microfoundation of the model, which decomposes agents' behaviour into price adjustments and deviations of the price level from its target. The empirical relevance of the NKPC is, however, a matter of debate as recent studies reveal that some supportive evidence depends crucially on the econometric methods applied. We show how to evaluate the features of the model using cointegration techniques and tests based on both single-behavioural equations and cointegrated VAR models. Our results indicate that the forward-looking part of the NKPC is most likely at odds with Norwegian data. By contrast, we establish a well-specified dynamic model interpreted as a standard backward-looking mark-up price equation. We also demonstrate that the dynamic mark-up model forecasts well post-sample and during a major change in the monetary policy regime, which certainly is strong evidence in favour of this model. Consequently, we conclude that taking account of forward-looking behaviour when modelling consumer price inflation in Norway seems unnecessary to arrive at a well-specified model by econometric criteria.
Keywords: C51; C52; E31; F31; 330; The New Keynesian Phillips Curve; mark-up pricing; single-equation estimation methods; encompassing tests; cointegrated vector autoregressive models and equilibrium correction models.